Pengaruh Dedak Padi Terfermentasi Menggunakan Fermentor Berbeda dalam Pakan Ikan Nila - Surianti; Hasrianti; Damis; Gibran, M. Halil; Wahyudi; Mahfud, Chairul Rusyd (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
One way to increase tilapia aquaculture production is to produce feed. Materials are easy to obtain, do not compete with the community and are cheap wrongthe other is rice bran. This study aims to determine the effect of fermented rice bran flour using various types of fermenters on the growth performanceand feed utilization efficiency of tilapia. This research was conducted inSidenreng Rappang Regency. The test animals used were tilapia larvae measuring ± 1.05 g. The maintenance container is a tarpaulin pond with a size of 1 m x 1 m x 1 m filled with 85 L of fresh water. The study was designed using a completely randomized design consisting of four treatmentsand three replications, thus there were 12 experimental units. The treatment was determined based on the fermenter used for fermenting rice bran flour, namely Bacillus sp., Lactobacillus sp., Aspergillus nigers and Yeast.The test feed was given to tilapia larvae whichwere stocked with 20 fish per container for 60 days of rearing. The data on specific growth rate and feed efficiency of tilapia were analyzed using analysis of variance (ANOVA) and water quality was analyzed descriptively based on the viability of tilapia.The results showed that tilapia fed fermented rice bran feed using Aspergillus nigers fermenter a significant effect on the specific growth rate and feed efficiency of tilapia. The optimal fermenter for hydrolyzing rice bran flour is using Aspergillus nigers.